Analysis of Online Promotion Strategies, Online Pricing, and Human Resource Quality in Enhancing Sales of WITROVE SMEs - Putra Gemilang, Adip; Setiyawan, Deny; Afinda, Mia; Roro Anita Septiani , Raden (ECOPRISE : Economic, Finance, and Business Enterprise Journal, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are crucial business entities that significantly contribute to economic growth, development, and the well-being of the population in Indonesia. Marketing plays a vital role in enabling companies to effectively communicate their offerings to a wide audience, thereby attracting potential consumers. The research methodology employed in this study involves utilizing an approach that relies on primary data, which is information gathered directly from original sources. The findings of this study highlight Witrove's promotional efforts, particularly its collaboration with Surabaya Fashion Week (SFW) in partnership with the local government, as well as its engagement with prominent influencers to enhance product visibility. However, a pricing disparity between Witrove and its competitors in the market has hindered consumer purchases of Witrove's products. Additionally, the study reveals that Witrove's workforce lacks proficiency in managing social media accounts and maintaining an active presence on online marketplaces.
Keywords: MSMEs; Digital Strategy; Promotion Strategy